Study of risk factors in myopic individuals among medical students in Chennai, Tamil Nadu - Arumugam, Seshadhri; Balabaskaran, S.; Abhilash, B. A.; Sowmiya, K.; Baalann, Krishna Prasanth; Surya, B. N. (Journal of Applied Pharmaceutical Research, 2023)
Background: The incidence of myopia is increasing at an alarming rate. Investigating the causes of myopia gives us a better understanding of it. This gives us better odds of preventing the occurrence and retarding the condition's progression. The study used a method called stratified sampling to select 100 individuals who were near-sighted. They belonged to the age of 17-30 years old and pursued medicine in the district of Kanchipuram. The role of risk factors was assessed through a questionnaire. Result: The percentage of subjects with low, medium, and high myopia was 77, 18, and 5, respectively. The role of heredity, diet, academic performance, time spent doing near work, and outdoor work was indeed found to play significant roles in the development and progression of myopia. Conclusion: The incidence of myopia is constantly increasing, especially in Asian countries. To prevent myopia and its complications, we need to take significant steps to reduce the risk factors that can be changed.